Rapid evolution of A(H5N1) influenza viruses after intercontinental spread to North America - Kandeil, Ahmed; Patton, Christopher; Jones, Jeremy C.; Jeevan, Trushar; Harrington, Walter N.; Trifkovic, Sanja; Seiler, Jon P.; Fabrizio, Thomas; Woodard, Karlie; Turner, Jasmine C.; Crumpton, Jeri-Carol; Miller, Lance; et al. (Nature communications, 2023)
Highly pathogenic avian influenza A(H5N1) viruses of clade 2.3.4.4b underwent an explosive geographic expansion in 2021 among wild birds and domestic poultry across Asia, Europe, and Africa. By the end of 2021, 2.3.4.4b viruses were detected in North America, signifying further intercontinental spread. Here we show that the western movement of clade 2.3.4.4b was quickly followed by reassortment with viruses circulating in wild birds in North America, resulting in the acquisition of different combinations of ribonucleoprotein genes. These reassortant A(H5N1) viruses are genotypically and phenotypically diverse, with many causing severe disease with dramatic neurologic involvement in mammals. The proclivity of the current A(H5N1) 2.3.4.4b virus lineage to reassort and target the central nervous system warrants concerted planning to combat the spread and evolution of the virus within the continent and to mitigate the impact of a potential influenza pandemic that could originate from similar A(H5N1) reassortants. Highly pathogenic avian influenza A(H5N1) viruses of clade 2.3.4.4b underwent an explosive geographic expansion in 2021 among wild birds and domestic poultry. Here, Kandeil et al. show that the Western movement of this clade was followed by reassortment with viruses circulating in wild birds in North America which resulted in different genotypes exhibiting a wide range of disease severity in mammal models (mice, ferrets, chicken) ranging from asymptomatic disease to severe neurological pathology.